FORMAL CODE-SWITCHING IN EFL SPEAKING COURSE - Jelimun, Maria Olga (Universitas Islam Sumatera Utara (UISU), 2025)
This study aims at determining the types, functions, and frequency of formal code-switching use in EFL Speaking course classrooms by second-year students of English Language Education Study Program students at Universitas Katolik Indonesia Santu Paulus Ruteng. The researcher used Hoffman's theory to find the types of code-switching and Gumperz's theory to find the functions of code-switching. This research was done through the descriptive mix method, using observation, documentation, and recording to collect data. This research result showed five types of code-switching used by second year students, particularly in formal interaction setting speaking class. The use of those five types of code-switching has shown different percentages. 21% Intra-sentential switching has been used, 32% inter-sentential switching has been used. Moreover, 5% establish continuity with the previous speaker has been used. 37% emblematic switching was used, and a change in pronunciation features was only 5%. Furthermore, based on the data findings, the researchers found that students frequently used emblematic switching in formal interaction when speaking.